Ahlquist, Irving (audio interview #5 of 5) - Ahlquist, Irving (b. 1916 - d. 2004); Briegel, Kaye, interviewer
INTERVIEW DESCRIPTION - This is the first of five interviews conducted in Ahlquist's office in the CSULB History Department. The audio quality of the interview is good. 1/12/1981